Do Medical Treatments Work for Work? Evidence from Breast Cancer Patients - N. Meltem Daysal; Mikkel Hasse Pedersen; William N. Evans; Mircea Trandafir (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We investigate the impact of adjuvant radiation therapy (RT) treatment on the labor market outcomes of breast cancer patients. In order to address the endogeneity in receipt of adjuvant radiotherapy, we use a 2SLS strategy that exploits plausibly exogenous variation in RT treatments due to changes in treatment guidelines. We find that adjuvant RT leads to significant improvements in employment and income. The gains are observed as early as three years after diagnosis and persist up to 10 years postdiagnosis. The main driver of these results seems to be reduced disability in the future.
Keywords: 330; Krebskrankheit; Strahlentherapie; Beschäftigungseffekt; Haushaltseinkommen; Dänemark